Small Bowel Video Capsule Endoscopy Guidance in Practice: Expert Opinion Report - Akyüz, Filiz; Ersoy, Osman; Erzin, Yusuf; Çavuş, Bilger; Bakkaloğlu, Oğuz; Akın, Ebru; Kav, Taylan; Akyüz, Ümit; Pata, Cengiz (Turkish Journal of Gastroenterology, 2023)
Capsule endoscopy, in clinical use since the 2000s, has disrupted the diagnosis of various small bowel diseases, especially obscuregastrointestinal bleeding. An overview of information on indications, contraindications, patient management, and patient preparationfor capsule endoscopy, which allows the evaluation of the entire gastrointestinal tract, will be helpful for both referrers and capsuleendoscopy. This review critically considers current evidence on the optimal clinical use of capsule endoscopy and addresses areas in the “gray zone.” Cite this article as: Akyüz F, Ersoy O, Erzin Y, et al. Small bowel video capsule endoscopy guidance in practice: Expert opinion report. Turk J Gastroenterol. 2023;34(S1):S2-S19.